At Different Speeds: Policy Complementarities and the Recovery from the Asian Crisis - Bruno Rocha (Asian Development Bank Institute (ADBI), 2009)
This paper begins with a short review and discussion of the literature on policy complementarities and their implications in terms of (sustainable) growth strategies and the possible emergence of a new policy making paradigm. Then, it provides a descriptive analysis of the effect on economic growth of complementarities in structural policies in the specific context of the post-Asian crisis recovery. The study resulted in the computation of a reform-level indicator and of a complementarity indicator RC for the economies most affected by the Asian crisis—Indonesia, Republic of Korea, Malaysia, and Thailand. The comparative analysis shows that these indicators, when applied to a more comprehensive group of policy areas, are related to faster recoveries; importantly, decreasing or low RCs are related to slower recoveries. Furthermore, immediate resilience to the crisis seems to be stronger when a broader, more coherent set of policies is already in place. In general, the analysis suggests that while augmenting the levels of the so-called orthodox policies is necessary, it is not sufficient to generate high, sustainable post-crisis growth trajectories, as those policies must be complemented with others and evolve in a coherent, complementary way.
hdl:11540/4179
Keywords: 330; complementarity; structural reforms; growth; recovery; Asian crisis; Wirtschaftskrise; Wirtschaftliche Anpassung; Wirtschaftsreform; Wirkungsanalyse; Indonesien; Südkorea; Malaysia; Thailand